The impact of demographics on health and health care race, ethnicity and other social factors - Kronenfeld, Jennie J. (Research in the sociology of health care, 2010)
Volume 28, The Impact of Demographics on Health and Healthcare: Race, Ethnicity and other Social Factors, focuses on differences in health and health care as linked to important social factors. The first section, Social Factors Leading to Differences in Health and Health Care, reviews basic material on the topic. The second section on Racial and Ethnic Factors in Differences in Health and Health Care is the largest section of the book, and includes 6 articles looking at racial disparities on a variety of topics such as knowledge of hepatitis C Virus, health services received and patients experiences in seeking health care, use of CAM (complementary and alternative medicine) services, and the role of social capital in class and race health disparities in health information seeking behaviour. The third section includes three articles focused on geographic and community factors. The fourth section has two articles on gender and age and gender and language. The fifth section has two articles on lifecourse issues such as maternal depression and hospice care.